International Survey of Family Law 2020 : 2020 edition / edited by Margaret Brinig. - Brinig, Margaret F. (Intersentia, 2020)
The International Society of Family Law is an independent, international, and non-political scholarly association dedicated to the study, research and discussion of family law and related disciplines. The Society's membership currently includes professors, lecturers, scholars, teachers, and researchers from more than 50 different countries, offering a unique opportunity for networking within a truly international family law community. The International Survey of Family Law is the annual review of the International Society of Family Law. It brings together reliable and clearly structured insights into the latest and most notable developments in family law from all around the globe. Chapters are prepared by an international team of selected experts in the field, usually covering 20 or more jurisdictions in each edition. The 2020 edition addresses issues that relate to the whole fabric of family life, from surrogacy, assisted reproduction and adoption, to the care of vulnerable adults and elderly people. The chapters are particularly diverse in this edition, dealing with family formation, the functioning of intact families and families during or post-dissolution. Further chapters examine the protection of children by international organisations. Once again, our authors include emerging scholars as well as highly regarded academics, judges and practitioners. With contributions by David Accioly de Carvalho, Martha Bailey, Malgorzata Balwicka-Szczyrba, Bastien Baret, Christine Bidaud, Claire Brunerie, Aurore Camuzat, Clara Delmas, Nina Dethloff, Ruina Feng, Éric Fongaro, Hugues Fulchiron, Melanija Jančić, Katharina Kaesling, Guillaume Kessler, Olga A. Khazova, Suzana Kraljic, Alenka Križnik, Torunn E. Kvisberg, Dongjin Lee, Xia Li, Ledina Mandija, Benyam Dawit Mezmur, Guillaume Millerioux, Najma Moosa, Amélie Panet-Marre, Antonio Jorge Pereira Júnior, Elizabeth S. Perry, Grant T. Riethmuller, Anne Scully-Johnson, Elaine E. Sutherland, Anna Sylwestrzak, Caroline Tiefenbach, Richard Vessaud and Mary Welstead.MARGARET BRINIG is Professor of Law Emerita at the University of Notre Dame. She is an elected member of the American Law Institute and part of the Executive Council of the International Society of Family Law.